Characterization of single microvesicles in plasma from glioblastoma patients. Issue 5 (17th December 2018) - Fraser, Kyle; Jo, Ala; Giedt, Jimmy; Vinegoni, Claudio; Yang, Katherine S; Peruzzi, Pierepaolo; Chiocca, E Antonio; Breakefield, Xandra O; Lee, Hakho; Weissleder, Ralph
Abstract: Background: Extracellular vesicles (EV) are shed by tumor cells but little is known about their individual molecular phenotypes and heterogeneity. While exosomes have received considerable attention, much less is known about larger microvesicles. Here we profile single microvesicles (MV) and exosomes from glioblastoma (GB) cells and MV from the plasma of patients. Methods: EV secreted from mouse glioma GL261 and human primary GBM8 cell lines as well as from the plasma of 8 patients with diagnoses of GB and 2 healthy controls were isolated and processed for single vesicle analysis. EV were immobilized on glass slides and the heterogeneity of vesicle and tumor markers were analyzed at the single vesicle level. Results: We show that (i) MV are abundant, (ii) only a minority of MV expresses putative MV markers, and (iii) MV share tetraspanin biomarkers previously thought to be diagnostic of exosomes. Using MV capture and staining techniques that allow differentiation of host cell and GB-derived MV we further demonstrate that (i) tumoral MV often present as <10% of all MV in GB patient plasma, and (ii) there is extensive heterogeneity in tumor marker expression in these tumor-derived MV. Conclusion: These results indicate that single MV analysis is likely necessary to identify rare tumoral MV populations and the single vesicle analytical technique used here can be applied to both MV and exosome fractions without the need for their separation from each other. These studies form the basis for using single EV analyses for cancer diagnostics. Abstract : 1. Large EV (microvesicles) are abundant in circulation in glioblastoma patients. 2. This study defines the molecular landscape of single microvesicles in circulation.